Behavior and design of stainless steel tubular member welded end connections - Kıymaz, Güven; SEÇKİN, EDİP (Techno-Press, Po Box 33, Yuseong, Daejeon 305-600, South Korea, 2014)
Among the various alternatives to make a steel tubular member connection, making a slotted and gusset plate welded connection is one of the most frequently preferred alternatives. This type of connection is essentially an end connection that is made by slotting the tube longitudinally, inserting the gusset plate and then placing longitudinal fillet welds at the tube-to-plate interface. In this paper an experimental study on the behaviour of such connections in stainless steel is presented. 24 specimens were tested under concentrically applied axial tensile forces for varying tube-to-gusset plate weld lengths. Both circular and box section members were considered in the test program. Load-deformation curves were obtained and comparisons were made in terms of strength and ductility. The results obtained from the study were then critically examined and compared with currently available design guidance for slotted gusset plate welded tubular end connections. It is noted that no specific rules exist in international specifications on structural stainless steel which cover the design of such connections. Therefore, the results of this study are compared with the existing design rules for carbon steel.
Keywords: stainless steel; tubular members; slotted and gusset plate welded connection; shear lag; tensile fracture; Gusset Plate Connections; Structural Design; Tension Members; Strength Method; Shear Lag; Sections; Construction; Capacity; Columns; Element